Organizing for digital servitization: A service ecosystem perspective - Sklyar, Alexey; Kowalkowski, Christian; Tronvoll, Bård; Sörhammar, David (Journal of business research, 2019)
Harnessing digital technology is of increasing concern as product firms organize for service-led growth. Adopting a service ecosystem perspective, we analyze interfirm and intrafirm change processes taking place as firms pursue digital servitization. The study draws on in-depth interviews with 44 managers involved in organizing activities in two multinational industry leaders. Our findings identify major differences between the two focal firms in terms of digital service-led growth and associated ecosystem-related activities. The study disentangles underlying processes of organizational change in the ecosystem and suggests that within-firm centralization and integration play a key role in the capacity to organize for digital servitization. For managers, the findings highlight the need to foster service-centricity in order to take full advantage of digitalization beyond purely technological benefits.